Development Of Smart Binoculars Learning For Trigonometry Materials In Middle Vocational School - Ferry Kurniawan; Moh. Mahfud Effendi; Siti Khoiruli Ummah (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
The purpose of this research is to develop smart binoculars learning media for trigonometry material in Vocational Schools so that it can help and facilitate mathematics teachers in explaining one of the concepts of trigonometry material. The type of research used in this research is Research and Development (R&D) while the development of instructional media refers to the modified Borg and Gall model, namely research and collection, planning, product draft development, expert validation, small-scale trials. The development has three criteria, namely valid, practical and effective. The results showed that obtained from filling out the validation sheet by the material expert and media expert validators were in the valid category. Furthermore, the practicality of smart binoculars learning media based on student response questionnaire the average student is satisfied with the learning experience using learning media and for the effectiveness of smart binoculars learning media get positive things because the evaluation of ten samples of students gets grades above minimal completeness criteria.